1979
DOI: 10.3758/bf03209688
|View full text |Cite
|
Sign up to set email alerts
|

Reacquisition of learned taste aversions

Abstract: SubjectsThe 84 male Sprague-Dawley rats ranged in ad-lib weight from 189 to 226 g just before the experiment. They were never removed from their steel wire home cages except for weighings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…The agreement of the present results with those of Danguir and Nicolaidis (1977), but not with those of Revusky and Coombes (1979), raises concern about why the results differ between the studies. One factor that probably contributed to Revusky and Coombes's failure to obtain slow reacquisition in at least some of their experiments is that their control groups received extensive preexposure (e.g., 10 exposures in some experiments and 8 in another experiment) to the flavor that was to be conditioned just prior to testing.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The agreement of the present results with those of Danguir and Nicolaidis (1977), but not with those of Revusky and Coombes (1979), raises concern about why the results differ between the studies. One factor that probably contributed to Revusky and Coombes's failure to obtain slow reacquisition in at least some of their experiments is that their control groups received extensive preexposure (e.g., 10 exposures in some experiments and 8 in another experiment) to the flavor that was to be conditioned just prior to testing.…”
Section: Discussionsupporting
confidence: 72%
“…Slow reacquisition is therefore not specific to the CER procedure of Bouton (1986) and Bouton and Swartzentruber (1989). The results support Danguir and Nicolaidis's (1977) finding of slow reacquisition with a CTA procedure, while conflicting with Revusky and Coombes's (1979) claim that slow reacquisition does not occur with a CTA procedure.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…For example, Danguir and Nicolaidis (1977) found extremely slow reacquisition; their results suggested that an aversion to saccharin could not be relearned following extinction. In contrast, Revusky and Coombes (1979) found that reacquisition .did occur. It was rapid compared to acquisition in a rest control group but comparable in rate to acquisition in a learning-experienced control group (Revusky & Coombes, 1979, Experiment 1).…”
mentioning
confidence: 47%
“…In taste-aversion learning in rats, rapid reacquisition has been observed (Revusky & Coombes, 1979), but "slow reacquisition" has been more common (Aguado, de Brugada, & Hall, 2001;Calton, Mitchell, & Schachtman, 1996;Hart, Bourne, & Schachtman, 1995). For example, Hart et al (1995) found that reacquisition was retarded relative to a "learningexperienced" control group that had received training and extinction with an orthogonal taste, for which there was little, if any, stimulus generalization.…”
mentioning
confidence: 99%